Management of open apex and tooth discoloration in maxillary central incisor: Case report - Yamin, Irfan F.; Trilaksana, Aries C.; Hikmah, Noor; Natsir, Nurhayaty; Nugroho, Juni J.; Dwiandhany, Wahyuni S. (Hasanuddin University, 2023)
Objective: The purpose of this case report is to describe the management of open apex and tooth discoloration in the maxillary central incisor.Methods: The patient had an accident 13 years ago. Intraoral examination showed tooth discoloration #8 and composite restoration on the mesial aspect of the tooth. The periapical radiograph showed an open apex and diffuse periapical radiolucency. The diagnosis was pulp necrosis with chronic periapical abscess. The patient was managed by root canal treatment with an apical plug using MTA and then internal bleaching using H2O2 is performed to treat tooth discoloration.Results: Trauma during root formation on anterior teeth can result in pulp necrosis with an open apex and tooth discoloration. This becomes a challenge because the condition of open apex complicates root canal obturation and presents aesthetic problems.Conclusion: The final treatment was composite restoration.